(untitled) (Communications in Computational Chemistry, 2022)
Several carbazole derivatives (V866, V867 and V868) as hole transporting materials (HTMs) in perovskite solar cells are designed to explore the functional group position effect on electrochemical properties. The material properties are studied on the first-principle calculations combined with the Marcus theory. The results illustrate that V866 (ortho-position) has the suitable HOMO energy level matched with the metal electrode (-5.1 eV) and the perovskite absorption layer (-5.4 eV). Moreover, the molecular planarity of HTMs with the ortho-position functional groups is improved, which enhances intermolecular face-to-face π-π stacking degree. Compared to V867 and V868, the largest hole mobility value (0.007 cm^2 V^-1 s^-1) of V866 is obtained due to its modified molecular planarity. Therefore, V866 (ortho-position) is indeed an excellent carbazole HTM. Our theoretical investigation of HTMs is helpful for understanding the hole transporting behaviors and developing higher performance HTMs.